1995
DOI: 10.5144/0256-4947.1995.344
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Obesity in a Saudi Infertility Population

Abstract: A menstrual history was taken from the female partners of all new infertility couples seen in our clinic between 1988 and 1990. The body mass index (Kg/M 2 ) was measured in all females. The ovulatory status was studied using a combination of serial transvaginal ultrasound investigations and progesterone measurements in the second half of the cycle in females with regular menstrual cycles or progesterone measurements one week before the expected onset of menstruation in females with oligomenorrhea. Amenorrheic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Among the women that were evaluated, it was found a prevalence of 42% of overweight (BMI 25-29 kg/m2) and 38% of obesity (BMI ≥ 30 kg/m2). With increasing BMI, it was possible to observe that the percentage of oligomenorrhea increased from 18% to 32%, the amenorrhea increased from 2% to 13% and the total percentage of anovulation increased from 32% to 55% (Hamilton et al ., 1995). …”
Section: Resultsmentioning
confidence: 99%
“…Among the women that were evaluated, it was found a prevalence of 42% of overweight (BMI 25-29 kg/m2) and 38% of obesity (BMI ≥ 30 kg/m2). With increasing BMI, it was possible to observe that the percentage of oligomenorrhea increased from 18% to 32%, the amenorrhea increased from 2% to 13% and the total percentage of anovulation increased from 32% to 55% (Hamilton et al ., 1995). …”
Section: Resultsmentioning
confidence: 99%
“…According to several epidemiological studies, the rate of obesity was reported between 13% and 70% in Saudi societies [1,2,3,4,5,6,7], and the rate of obesity continues to increase among Saudi adults [8]. Obesity has been associated with multiple preventable comorbidities and health outcomes, and it increases the risk of mortality [9], diabetes [10], cancer [11], heart disease [12], liver [13], and Helicobacter pylori infection [14].…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is known as causative factor for the development of breast cancer and is associated with dismal prognosis in breast cancer patients because of delayed diagnosis among overweight women or the growth and spread of breast cancer may be more rapid in obese women and consequently, obese women would tend to have more recurrences [11]. In Saudi Arabia 80% of premenopausal women are either overweight or obese which alarms the grave prognosis of breast cancer as compared to other parts of the world [12]. However impact of obesity or increased BMI on locoregional control in breast doi: 10.7243/2052-5966-2-1…”
Section: Discussionmentioning
confidence: 99%